2014
DOI: 10.1027/1618-3169/a000256
|View full text |Cite
|
Sign up to set email alerts
|

Biases in Spatial Bisection Induced by Viewing Male and Female Faces

Abstract: Research on visual attention triggered by face gender is still relatively sparse. In the present study, three experiments are reported in which male and female participants were required to estimate the midpoint of a line (i.e., the "line bisection task"): at each end of the line a face was presented. Depending on the experimental condition, faces could be of the same gender (i.e., two males or two females) or the opposite gender. Experiments 1 and 2 converged in showing that when a male face was presented at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…When we take into account the performance of all participants in the current investigation, our results are consistent with two previous studies (Cattaneo et al, 2014a ; Hatin and Sykes Tottenham, 2016 ), showing that happy faces decrease pseudoneglect, reducing the leftward bisection error when compared to Baseline (empty circle flanked lines), as well as to neutral and negative (sad faces) stimuli. The extent of the pseudoneglect in our results is substantially comparable to previous studies (Cattaneo et al, 2014a , b ; Hatin and Sykes Tottenham, 2016 ). The neurobiological underpinnings of the leftward bias (pseudoneglect) are likely to depend on hemispheric asymmetries in attentional frontoparietal networks, which are modulated by emotional processing (de Schotten et al, 2005 ; Corbetta et al, 2008 ; Bartolomeo and Malkinson, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…When we take into account the performance of all participants in the current investigation, our results are consistent with two previous studies (Cattaneo et al, 2014a ; Hatin and Sykes Tottenham, 2016 ), showing that happy faces decrease pseudoneglect, reducing the leftward bisection error when compared to Baseline (empty circle flanked lines), as well as to neutral and negative (sad faces) stimuli. The extent of the pseudoneglect in our results is substantially comparable to previous studies (Cattaneo et al, 2014a , b ; Hatin and Sykes Tottenham, 2016 ). The neurobiological underpinnings of the leftward bias (pseudoneglect) are likely to depend on hemispheric asymmetries in attentional frontoparietal networks, which are modulated by emotional processing (de Schotten et al, 2005 ; Corbetta et al, 2008 ; Bartolomeo and Malkinson, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…To confirm previous studies that employed the bisection task (Cattaneo et al, 2014a , b ), we first analyzed the global performance of the 60 participants (not considering the differences in trait anxiety scores).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while some researchers have shown no evidence of own-sex bias in face recognition in children [46], others have demonstrated that both male and female infants show preference for female body shape [47] and faces [48]. Adults also show no evidence of own-sex bias, demonstrating the same attentional bias toward male over female faces, especially in threat or anger contexts [49]. Further, at least two meta-analyses on the effect of gender on emotion processing have reported no such own-gender bias across a wide age range [5051].…”
Section: Discussionmentioning
confidence: 99%
“…Second, our experimental materials included the use of only female facial expressions, and it is unclear whether male faces are perceived as more threatening than female faces. 54 Finally, neutral emotional faces have not been used as experimental materials in our research. We are not sure whether parents of children with ASD avoid looking at the eyes of neutral faces.…”
Section: Limitationmentioning
confidence: 99%